2022
DOI: 10.1038/s41467-022-34667-x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics of Parkinson’s disease implicates the gut microbiome in multiple disease mechanisms

Abstract: Parkinson’s disease (PD) may start in the gut and spread to the brain. To investigate the role of gut microbiome, we conducted a large-scale study, at high taxonomic resolution, using uniform standardized methods from start to end. We enrolled 490 PD and 234 control individuals, conducted deep shotgun sequencing of fecal DNA, followed by metagenome-wide association studies requiring significance by two methods (ANCOM-BC and MaAsLin2) to declare disease association, network analysis to identify polymicrobial cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
183
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(205 citation statements)
references
References 74 publications
21
183
1
Order By: Relevance
“…Coverage depth helps to understand the abundance of a microorganism, and comparing abundance between PD and control group might indicate association of a microorganism to the disease. A MAG that was annotated as Alistipes onderdonkii had significantly (p < 0.1) more coverage depth in the PD group, which was similarly reported in other studies with high abundance of Alistipes in the PD group [ 51,52,53 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Coverage depth helps to understand the abundance of a microorganism, and comparing abundance between PD and control group might indicate association of a microorganism to the disease. A MAG that was annotated as Alistipes onderdonkii had significantly (p < 0.1) more coverage depth in the PD group, which was similarly reported in other studies with high abundance of Alistipes in the PD group [ 51,52,53 ].…”
Section: Discussionsupporting
confidence: 85%
“…A MAG that was annotated as Alistipes onderdonkii had significantly (p < 0.1) more coverage depth in the PD group, which was similarly reported in other studies with high abundance of Alistipes in the PD group [ 51,52,53 ].…”
Section: Microdiversity Analysis Indicated That the Mags Annotated As...supporting
confidence: 84%
“…Moreover, a recent study using shotgun metagenomic sequencing of Parkinson’s disease patients has shown that eighty-four species were associated with Parkinson’s disease, with 55 species more and 29 species less exist in Parkinson’s disease compared to healthy subjects. In addition, 34 genera more and 1 genus less present in Parkinson’s disease compared to healthy controls [ 48 ].…”
Section: Bas and Gut Microbiotamentioning
confidence: 99%
“…Furthermore, a recent preprint demonstrates that gut bacteria can also influence the production of host amyloids, as bacterial nitrate reduction stimulates the intestinal aggregation of α-synuclein [ 106 ]. These results, combined with the growing amount of metagenomic data from patients with Parkinson’s disease and healthy individuals, suggest that multiple, distinct microbiome-dependent cellular and molecular mechanisms may combine to drive disease in patients with Parkinson’s disease [ 107 ].…”
Section: Introductionmentioning
confidence: 99%